(untitled) (International Journal of Nursing Education, 2020)
Introduction: Disclosure of HIV serostatus is critical to controlling the spread of HIV, and understandingthe experience for disclosure enhances the development of prevention interventions and ultimately leads tobetter control of the spread of the disease. The present narrative review aimed to synthesize literature on theeffects of positive HIV status disclosure on sexual behaviour change.Method: Anarrative review design was utilized. Literature search of articles was from the followingdatabases; Scopus, Science Direct, PUBMED, OVID and Google scholar. The searches were conductedfrom August 2019 to June 2020. The qualitative analysis was used to presented data into themes.Results: The main findings were discussed under four thematic domains: 1) disclosure, 2) number of sexualpartners, 3) type of sexual partners and 4) use condoms.Conclusion: The narrative review presents evidence on; how patients revealing their HIV positive statusto their sexual partner(s), family members, or others in their social circle are associated to better, less riskysexual behaviors. This finding implies that when people living with HIV disclose their status, they are mostlikely to; 1) have less sexual partners, 2) use condoms and 3) minimize casual/temporary sex. The behaviorchange brought by the positive HIV status disclosure can significantly reduce the transmission of HIV withinthe society.